Resistin in pregnancy: Analysis of determinants in pairs of umbilical cord blood and maternal serum. Issue 2 (June 2021) - Floeck, Anne; Ferrari, Nina; Joisten, Christine; Puth, Maria T.; Strizek, Brigitte; Dolscheid-Pommerich, Ramona; Gembruch, Ulrich; Merz, Waltraut M.
Abstract: Objective: Despite intensive research on the cytokine resistin only few studies investigated mother-newborn-pairs during healthy pregnancy and reported about interactions with clinical obstetric variables or other cytokines. Comparison of existing studies is difficult due to differences between assays, sample collection, gestational age, definition of healthy controls and patient characteristics. Furthermore, differences between rodent models and humans do not allow for a direct comparison. Methods: In this cross-sectional, prospective study 109 healthy mother-newborn pairs were analyzed. Maternal venous blood samples were taken on admission to the labor ward; newborn venous blood samples were drawn from the placental part of the umbilical cord (UC), immediately after clamping. Resistin, leptin, adiponectin, TNF-α, IL-6 and brain derived neurotrophic factor (BDNF) serum concentrations were measured with commercially available immunoassays. Determinants of maternal and newborn resistin levels were analyzed using simple and multiple linear regression. Results: UC resistin levels were higher than maternal concentrations (median 17.69 ng/mL, IQR 7.36 vs. median 8.04 ng/mL, IQR 4.30). Correlation between UC and maternal resistin levels was moderate (R = 0.503, p < 0.01). In multiple regression analysis levels of maternal resistin and newborn TNF-α remained significant determining factors for UC resistin levels. Gestational age and maternal BDNF-levels remained significant factors for maternal resistin levels. Conclusion: In healthy, term newborns and their respective mothers a positive correlation between maternal and newborn levels and an association with gestational age around term can be found and point to a placental source of resistin. Further investigations are needed to clarify the possible contribution of transplacental transport of resistin into the fetal circulation. Except for gestational age most of the clinical obstetric variables tested do not seem to be determining factors for fetal or maternal resistin. Interactions of resistin with other cytokines like TNF-α and BDNF could be the missing link for the conflicting results in literature.